Fragmentation of Dakwah Media: Exploring Exclusive Islam in Indonesia Post-Reform Popular Islamic Novels - Muhamad Taufik Kustiawan; Mhd. Rasidin; Doli Witro; Darti Busni; Mufti Labib Jalaluddin (Universitas Islam Negeri Mataram, 2023)
This article aims to highlight Islamic exclusivism in the form of popular Islamic novelS for children’s reading books in Indonesia after the reform of 1998. Building on the media theory of Gill Branston and Roy Stafford, this study explains Islamic pop novels as Islamic educational materials from a semiotic approach, structuralism, and critical discourse analysis. In particular, this study uses qualitative research methods by descriptively analyzing the reading of Islamic pop novels spreading in the Qur’anic Education Centre in Central Java. The results showed that since the Reformation, the movement used books, newsletters, magazines, and children’s readings of Islamic pop novels to shape the religious thoughts of urban Muslim children and youth in Indonesia. There is hardly a story related to diversity, the value of tolerance, and mutual respect between religious people in those materials. The awareness of religious comprehension in children's reading seems exclusive. It must be realized by various parties that the media utilizing Islamic literature is very influential on the growth and development of children's religious thinking in the educational space in the metropolis.